Göteborgs blå struktur - Ekfeldt, Frida (2007)
Gothenburg municipality has a lot of natural water. This paper enhances the function and importance of water in the city. It also deals with the problems of sewage water and flooding. Gothenburg has reached an advanced stage of water planning. By developing a Waterplan, the municipality highlight that water has an important position in the urban planning. In the Waterplan all watercourses are considered as units and no overall picture is proposed. This paper describes an overall picture of the watercourses in the municipality. Göta Älv, the moat and the canals are enhanced as structuring elements.